Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/slct.201902109
|View full text |Cite
|
Sign up to set email alerts
|

2,3‐Di(thiophen‐2‐yl)quinoxaline Amine Derivatives: Yellow‐Blue Fluorescent Materials for Applications in Organic Electronics

Abstract: In this work, we have designed and synthesized new donoracceptor (D-A) type, 2,3-di(thiophen-2-yl)quinoxaline based amine derivatives (2-10). These compounds contain diaryl/ heterocyclic amine segment and quinoxaline core as an electron donor and acceptor respectively. The synthesized molecules were fully characterized by standard spectroscopic techniques. Absorption spectra of all compounds showed intramolecular charge transfer (ICT) transition in the range of 390 to 461 nm. Dyes emit in yellow-blue region wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…In comparison, when a second thiophene ring was added to the quinoxaline sub-unit (L 10 H), a lower ε value (1.0 × 10 4 M −1 cm −1 ) at λ max 378 nm was recorded. It should be noted that previous studies have shown that charge transfer can be observed from the thiophene ring donors to the quinoxaline acceptors, 8 often explaining the observation of lower energy absorption bands. 29 L 1-11 H were analysed by steady state luminescence spectroscopy (Table 2, Fig.…”
Section: Photophysical Properties Of 2-(thienyl)-quinoxaline Speciesmentioning
confidence: 93%
See 1 more Smart Citation
“…In comparison, when a second thiophene ring was added to the quinoxaline sub-unit (L 10 H), a lower ε value (1.0 × 10 4 M −1 cm −1 ) at λ max 378 nm was recorded. It should be noted that previous studies have shown that charge transfer can be observed from the thiophene ring donors to the quinoxaline acceptors, 8 often explaining the observation of lower energy absorption bands. 29 L 1-11 H were analysed by steady state luminescence spectroscopy (Table 2, Fig.…”
Section: Photophysical Properties Of 2-(thienyl)-quinoxaline Speciesmentioning
confidence: 93%
“…We have sought to expand our repertoire of quinoxaline-containing ligands and considered the combination of the quinoxaline moiety with an electron rich thiophene-based donor component. There have been a small number of previous reports detailing the unique photophysical properties that result from the combination of thiophene and quinoxaline units in organic donor–acceptor (D–A) assemblies, 7 including compounds bearing a 2,3-di(thiophen-2-yl)quinoxaline core, 8 which displayed prominent intramolecular charge transfer (ICT) character. More recently, work on V-shaped D–A–D chromophores, where 1,5-thiophenylene acts as a π-conjugated spacer unit and either 6-cyano or 6,7-difluoroquinoxaline functioned as electron-acceptors have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the HOMO and LUMO values were found in the range of −4.90 to 5.70 eV and −3.10 to −3.36 eV, respectively. 70 For the pyrene-substituted oxadiazole moiety, Najare et al developed a new molecule with proper hole and electron transfer (Figure 43). Differential scanning calorimetry and thermogravimetric analysis studies proved that the molecule has excellent stability for application in optoelectronics in the range of 204 -366 °C.…”
Section: Progress Of Blue Light Emitters In Indiamentioning
confidence: 99%
“…Previously, Tang's research group reported a series of pyrazine derivatives that show AIE feature due to push-pull electronic structure. 37 To further verify the AIE properties, the compounds 1-4 were dissolved in a good solvent (THF), and the ratio of poor solvent (water) was gradually increased. For example, compound 1 shows weak blue fluorescence in pure THF solution with the maximum emission peak of 413 nm (Fig.…”
Section: Study the Aie Propertymentioning
confidence: 99%